Study of dental records archive: global perspective - Guimarães, Maria Inês; Loibl, Beatriz; Silva, Jéssica; Rodrigues, Carolina; Silva, Madalena; Mira de Almeida, Sofia; Silveira, Augusta (Scientific Letters, 2024)
Background: Forensic medicine is a field that applies medical knowledge to legal issues focusing on human identification. Dental records are of great importance in this area due to the valuable information they can provide. Objective: The aim of this research is to examine the worldwide participation and dedication to the preservation of dental records, while also noting variations in this practice among different nations. Methods: An email was sent to the representative dentistry associations in several countries to inquire about their awareness of the importance of preserving dental records. The addresses were collected from the official website of the International Dental Federation. International SOS has determined the risk category and classified it into five levels, considering variables such as military forces, state of war, government and legal control, among others. These levels are high risk, medium risk, low risk and insignificant risk. Results: The Portuguese Dental Association suggests that dental records should be kept for at least 20 years after the last treatment. Several countries, including Israel, Russia, Finland, Iceland, Norway, and South Africa, which are classified as medium or high risk, attach great importance to such procedures, with a minimum retention period of 75 years. However, it may be advisable for Guinea-Bissau and Brazil to consider implementing regulations or extending their minimum periods (currently at a minimum of 4 years) to mitigate potential risks. Conclusions: At a global perspective, it was found that the countries surveyed did not always have an ideal correlation between the level of risk and awareness of the importance of complete and updated dental records. It is recommended that all nations enhance the implementation of dental records, ensuring they are stored effectively and are accessible. With the world constantly changing, it is important to constantly update these elements.